Lysophosphatidic Acid Inhibits Apoptosis Induced by Cisplatin in Cervical Cancer Cells. (20th August 2015) - Sui, Yanxia; Yang, Ya; Wang, Ji; Li, Yi; Ma, Hongbing; Cai, Hui; Liu, Xiaoping; Zhang, Yong; Wang, Shufeng; Li, Zongfang; Zhang, Xiaozhi; Wang, Jiansheng; et al.
Abstract : Cervical cancer is the second most common cause of cancer death in women worldwide. Lysophosphatidic acid (LPA) level has been found significantly increased in the serum of patients with ovarian, cervical, and colon cancers. LPA level in cervical cancer patients is significantly higher than in healthy controls. LPA receptors were found highly expressed in cervical cancer cells, suggesting LPA may play a role in the development of cervical cancer. The aim of this study is to investigate the effect of LPA on the apoptosis induced by cisplatin (DDP) in cervical cancer cell line and the underlying changes in signaling pathways. Our study found that cisplatin induced apoptosis of Hela cell through inhibiting expression of Bcl-2, upregulating the expression of Bax, Fas-L, and the enzyme activity of caspase-3 (p < 0.05 ); LPA significantly provided protection against the apoptosis induced by cisplatin by inhibiting the above alterations in apoptotic factor caused by cisplatin (p < 0.05 ). Moreover, PI3K/AKT pathway was found to be important for the LPA antiapoptosis effect, and administration of PI3K/AKT partially reversed the LPA-mediated protection against cisplatin-induced apoptosis (p < 0.05 ). These findings have shed new lights on the LPA bioactivity in cervical cancer cells and pointed to a possible sensitization scheme through combined administration of PI3K inhibitor and cisplatin for better treatment of cervical cancer patients, especially those with elevated LPA levels.